The Impact of Hepatitis C on Complication Rates After Revision Total Knee Arthroplasty: A Matched Cohort Study - Bailey J. Ross, MD; Austin J. Ross, MD; Matthew W. Cole, MD; George N. Guild, III, MD; Olivia C. Lee, MD; William F. Sherman, MD, MBA (Arthroplasty Today, 2022)
Background: It is unclear if hepatitis C (HCV) negatively impacts outcomes of revision total knee arthroplasty (rTKA). The purpose of this study was to compare complication rates after rTKA for patients with HCV vs matched controls. Methods: A retrospective cohort study was conducted using the PearlDiver database (PearlDiver Inc., Colorado Springs, CO). Patients with HCV who underwent rTKA (n = 1448) were matched 1:4 with controls (n = 5792) on age, sex, and several comorbidities. Rates of medical complications within 90 days and prothesis-related complications within 2 years postoperatively were compared with logistic regression for (1) patients with vs without HCV and (2) HCV patients who underwent aseptic vs septic rTKA. Results: Relative to controls, patients with HCV exhibited significantly higher rates of medical complications (27.7% vs 20.9%; odds ratio [OR] 1.47), periprosthetic fractures (2.3% vs 1.1%; OR 2.20), all-cause repeat rTKA (11.7% vs 9.4%; OR 1.29), and repeat rTKA for prosthetic joint infection (PJI) (6.7% vs 3.6%; OR 1.92). Within the HCV cohort, HCV patients with initial septic rTKA exhibited significantly higher rates of medical complications (41.7% vs 22.7%; OR 2.39), all-cause subsequent rTKA (15.9% vs 10.2%; OR 1.67), and repeat rTKA for PJI (15.9% vs 3.4%; OR 5.39). Conversely, HCV patients with initial aseptic rTKA exhibited significantly higher rates of aseptic loosening (2.6% vs 7.4%; OR 0.33). Conclusions: Patients with HCV exhibited significantly higher rates of medical and prosthesis-related complications after rTKA than controls. Among patients with HCV, initial septic rTKA was associated with significantly higher rates of medical complications, repeat rTKA, and PJI.